(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Students' academic performance and emotional intelligence (EI) were examined. The study's goals were to: (1) describe the sociodemographic profile of the respondents; (2) measure their emotional intelligence (EI); (3) calculate their academic performance using the General Weighted Average (GWA); (4) investigate the relationship between academic performance and emotional intelligence; (5) identify variations in academic performance and EI across demographic factors; and (6) suggest an intervention program to improve academic outcomes and emotional intelligence. A correlational, quantitative study design was used. A validated questionnaire was used to gather the data, which were then examined using one-way ANOVA, Pearson's correlation coefficient, and descriptive analysis. 203 of the respondents were female, between the ages of 18 and 20, and from low-income families. The results showed that pupils had excellent emotional intelligence, especially when it came to motivation and self-awareness. In general, academic achievement was satisfactory. A statistically significant but weak inverse relationship (r = -0.10975, p = 0.0133) between emotional intelligence and academic achievement was found using Pearson's correlation analysis, indicating that higher EI is linked to higher grades. When respondents were categorized based on sociodemographic traits, one-way ANOVA findings revealed no significant differences in EI or academic achievement. These results suggested that emotional intelligence had a moderate and consistent impact on academic achievement across all demographic groups. Based on the findings, the study suggested that CBA students develop their emotional competencies by implementing an Emotional Intelligence Enhancement Program (EIEP). Marinduque State University could generate graduates who are socially responsible, emotionally mature, and intellectually capable of handling the challenges of modern society by incorporating EI development into academic and student activities.